(Invited) Reliability Study of RF Power Amplifiers with GaN-on-SiC HEMTs. (23rd August 2016) - Lang, Jenny; Lim, Jang-Kwon; Hellen, Johan; Nilsson, Torbjörn M.J.; Schodt, Bo; Poder, Ralf; Belov, Ilja; Bakowski, Mietek; Leisner, Peter
Abstract : RF power amplifier demonstrators containing each one GaN-on-SiC, HEMT, CHZ015A-QEG, from UMS in SMD quad-flat noleads package (QFN) were subjected to thermal cycles (TC) and power cycles (PC) and evaluated electrically, thermally and structurally. Two types of lead-free solders (Sn63 Pb36 Ag2 and SnAgCu (SAC305)) and two types of TIM materials (NanoTIM and Tgon™ 805) for PCB attachment to liquid cold plate were tested for thermo-mechanical reliability. Changes in electrical performance of the devices namely reduction of the current saturation value, threshold voltage shift, increase of the leakage current and degradation of the HF performance were observed as a result of an accumulated current stress during PC. No significant changes in the investigated solder or TIM materials were observed.